2007
DOI: 10.1152/ajpendo.00696.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human organic anion transporter 4 by progesterone and protein kinase C in human placental BeWo cells

Abstract: Human organic anion transporter 4 (hOAT4) belongs to a family of organic anion transporters that play critical roles in the body disposition of clinically important drugs, including anti-human immunodeficiency virus therapeutics, anti-tumor drugs, antibiotics, antihypertensives, and anti-inflammatories. hOAT4 is abundantly expressed in the placenta. In the current study, we examined the regulation of hOAT4 by pregnancy-specific hormones progesterone (P4) and 17␤-estradiol (E2) and by protein kinase C (PKC) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…PKC activation decreased surface levels of OAT1, OAT4, OATP2B1, and OATP1A2 without affecting total protein levels of these transport proteins after short-term treatment with a PKC activator for up to 1 hour (Zhou et al, 2007(Zhou et al, , 2011Zhang et al, 2008Zhang et al, , 2010Köck et al, 2010). Rapid downregulation of transport function by PKC activation is associated with increased phosphorylation of OATP2B1 (Köck et al, 2010), the brain glutamate/aspartate transporter GLAST-1 (Conradt and Stoffel, 1997), as well as dopamine (Huff et al, 1997) and serotonin transporters (Jayanthi et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PKC activation decreased surface levels of OAT1, OAT4, OATP2B1, and OATP1A2 without affecting total protein levels of these transport proteins after short-term treatment with a PKC activator for up to 1 hour (Zhou et al, 2007(Zhou et al, , 2011Zhang et al, 2008Zhang et al, , 2010Köck et al, 2010). Rapid downregulation of transport function by PKC activation is associated with increased phosphorylation of OATP2B1 (Köck et al, 2010), the brain glutamate/aspartate transporter GLAST-1 (Conradt and Stoffel, 1997), as well as dopamine (Huff et al, 1997) and serotonin transporters (Jayanthi et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…The function of several human transport proteins is regulated by PKC activation. For example, PKC activation downregulates transport function of organic anion transporter (OAT) 1 (Zhang et al, 2008), OAT3 (Duan et al, 2010), and OAT4 (Zhou et al, 2007;Zhang et al, 2010); OATP2B1 (Köck et al, 2010) and OATP1A2 (Zhou et al, 2011); efflux transport protein P-glycoprotein (P-gp) (Miller et al, 1998); and multidrug resistance protein (MRP)2 (Kubitz et al, 2001). OATP1B3 has putative PKC phosphorylation sites as predicted by Scansite 3 (Obenauer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the regulation mechanism of hOAT4 in the kidney has begun to be explored, its regulation mechanism in the placenta is largely unknown. Zhou and co-workers have shown that the function of hOAT4 was down regulated both by activation of PKC and by pregnancy-specific hormones progestetone in placental BeWo cells (Zhou et al, 2007). However, they have reported that progesterone-induced down regulated hOAT4 function is independent on PKC pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kikuchi et al [35] discovered that promoter methylation could down regulate OAT function. At post-translational level, Protein Kinase C (PKC) regulated OAT functions through carrier mediated trafficking [37][38][39][40][41]. In addition, OAT activities could also be manipulated by phosphorylation at serine residue, or by epidermal growth factor [42][43][44][45].…”
Section: Transporter Function and Tssue Distribution Of Oatsmentioning
confidence: 99%